Validation of a targeted gene panel sequencing for the diagnosis of hereditary chronic liver diseases - Ronzoni, Luisa; Marini, Ilaria; Passignani, Giulia; Malvestiti, Francesco; Marchelli, Daniele; Bianco, Cristiana; Pelusi, Serena; Prati, Daniele; Valenti, Luca (Frontiers in Genetics, 2023)
Background: The cause of chronic liver diseases (CLD) remains undiagnosed in up to 30% of adult patients. Whole-Exome Sequencing (WES) can improve the diagnostic rate of genetic conditions, but it is not yet widely available, due to the costs and the difficulties in results interpretation. Targeted panel sequencing (TS) represents an alternative more focused diagnostic approach. Aims: To validate a customized TS for hereditary CLD diagnosis. Methods: We designed a customized panel including 82 CLD-associated genes (iron overload, lipid metabolism, cholestatic diseases, storage diseases, specific hereditary CLD and susceptibility to liver diseases). DNA samples from 19 unrelated adult patients with undiagnosed CLD were analyzed by both TS (HaloPlex) and WES (SureSelect Human All Exon kit v5) and the diagnostic performances were compared. Results: The mean depth of coverage of TS-targeted regions was higher with TS than WES (300x vs 102x; p<0.0001). Moreover, TS yielded a higher average coverage per gene and lower fraction of exons with low coverage (p<0.0001). Overall, 374 unique variants were identified across all samples, 98 of which were classified as “Pathogenic” or “Likely Pathogenic” with a high functional impact (HFI). The majority of HFI variants (91%) were detected by both methods; 6 were uniquely identified by TS and 3 by WES. Discrepancies in variant calling were mainly due to variability in read depth and insufficient coverage in the corresponding target regions. All variants were confirmed by Sanger sequencing except two uniquely detected by TS. Detection rate and specificity for variants in TS-targeted regions of TS were 96.9% and 97.9% respectively, whereas those of WES were 95.8% and 100%, respectively. Conclusion: TS was confirmed to be a valid first-tier genetic test, with an average mean depth per gene higher than WES and a comparable detection rate and specificity.